Status of Women in Hindu Society - Chutia, Sanjib; Boruah, Jimpi; Bharali, Rumi (Journal of Innovation in Education and Social Research, 2023)
Women play an important role in Indian society. The status of women in any society is the index of the standard of its social organization. The standard of a society rises and falls in correlation with the rise and falls in the status of women. The Hindu society has always dynamic. The status of women in it has consequently always changed. In this paper discuss the changing status of women from ancient to modern society.